Ex vivo expanded human regulatory T cells promote cholesterol efflux and PON1 expression in oxLDL-exposed macrophages via gap junction-mediated cAMP transfer - Albany, Caraugh Jane; Mastronicola, Daniela; Popov, Momchil; Stroukov, Wladislaw; Wierzbicki, Anthony S.; Martinez-Nunez, Rocio Teresa; Lombardi, Giovanna; Scottà, Cristiano (Frontiers in Immunology, 2025)
Lipid-driven inflammation contributes to the development of atherosclerosis, and regulatory T cells (Tregs) have been proposed to influence macrophage responses to lipid stress. While adoptive Treg transfer has been shown to be safe in clinical studies, the mechanisms by which Tregs modulate macrophage lipid handling remain incompletely understood. In this study, we investigated the effects of ex vivo–expanded human Tregs on primary monocyte-derived M2-like macrophages exposed to oxidized low-density lipoprotein (oxLDL) in an in vitro coculture system. We assessed macrophage phenotype, gene expression, and cholesterol accumulation using flow cytometry, RNA sequencing, and western blotting. Our data show that coculture with Tregs attenuated oxLDL-induced pro-inflammatory responses and reduced intracellular lipid accumulation in macrophages. Mechanistically, we found evidence that Tregs transfer cyclic AMP (cAMP) into macrophages, which enhanced the ABCA1-mediated cholesterol efflux pathway and increased expression of paraoxonase-1 (PON1). These findings provide mechanistic insight into how Tregs modulate macrophage responses to oxLDL under controlled in vitro conditions. They highlight potential pathways through which Tregs may regulate macrophage lipid metabolism and inflammatory activity. Further in vivo studies will be essential to determine the physiological significance and therapeutic potential of these mechanisms.